Quantitative proteomics suggests changes in the carbohydrate metabolism of maize in response to larvae of the belowground herbivore Holotrichia parallela - Yu Pan; Shiwen Zhao; Zhun Wang; Xiao Wang; Xinxin Zhang; Yunshuo Lee; Jinghui Xi (PeerJ, 2020)
The larvae of Holotrichia parallela, a destructive belowground herbivore, may cause yield losses of up to 20% in maize in a typical year. To understand the protein-level mechanisms governing the response of maize to this herbivore, tandem mass tag (TMT) quantitative proteomics was used for the comparative analysis of protein abundance in the maize roots after H. parallela larval attack. A total of 351 upregulated proteins and 303 downregulated proteins were identified. Pathway enrichment analysis revealed that the differentially abundant proteins (DAPs) were most strongly associated with carbohydrate and energy metabolism pathways, such as glycolysis, pentose phosphate pathway and fructose and mannose metabolism. Most glycolysis-related proteins were significantly induced. In addition, H. parallela larval attack decreased the glucose concentrations in the roots. This study demonstrates that maize can manipulate carbohydrate metabolism by modifying glycolysis and pentose phosphate pathway response to root-feeding herbivorous attackers. The results of this study may help to establish a foundation for further functional studies of key protein-mediated responses to H. parallela larvae in maize.